2013
DOI: 10.1212/wnl.0b013e31829a33f8
|View full text |Cite
|
Sign up to set email alerts
|

Brain network connectivity assessed using graph theory in frontotemporal dementia

Abstract: Global and local functional networks are altered in bvFTD, suggesting a loss of efficiency in information exchange between both distant and close brain areas. Altered brain regions are located in structures that are closely associated with neuropathologic changes in bvFTD. Aberrant topology of the functional brain networks in bvFTD appears to underlie cognitive deficits in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
135
1
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(178 citation statements)
references
References 40 publications
24
135
1
5
Order By: Relevance
“…In line with these results, studies assessing cognitive impairments of different etiology (e.g., developmental or neurodegenerative; Itahashi et al, 2014;Agosta et al, 2013;Van den Heuvel et al, 2013;Buckner et al, 2009) suggest that hub connectivity plays a role in cognition ( Van den Heuvel & Sporns, 2013b).…”
Section: Discussionmentioning
confidence: 66%
“…In line with these results, studies assessing cognitive impairments of different etiology (e.g., developmental or neurodegenerative; Itahashi et al, 2014;Agosta et al, 2013;Van den Heuvel et al, 2013;Buckner et al, 2009) suggest that hub connectivity plays a role in cognition ( Van den Heuvel & Sporns, 2013b).…”
Section: Discussionmentioning
confidence: 66%
“…28 Interestingly, hubs seem to be especially sensitive to such a network pathology across many different neurologic disorders, stressing the clinical relevance of normal hub functioning. [28][29][30] To ensure comparison with other studies, we defined the hub-rich DMN and FPN on the basis of an anatomic atlas. However, future studies are needed to select hub and nonhub regions in a fully data driven way.…”
Section: Structural Brain Measures White Matter (Wm) Lesions Werementioning
confidence: 99%
“…It has been postulated that decreased functional integrity of the salience network may contribute to the failure to deactivate the DMN [46]. A recent study employing small world analysis (assessment of clustering of regions and their connectivity in the brain) detected a lack of cortical hubs in the frontal cortices in bvFTD [57]. A study focusing on functional connectivity and the genetic background in bvFTD has shown that there was no significant difference in frontoinsular connectivity within the salience network between nonsymptomatic MAPT, and GRN carriers and healthy participants.…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%